A colaboração dos grupos de referência na escolha do voto dos eleitores - Granja , Carlos Henrique Loureiro (2022)
This study aims to analyze how reference groups in virtual communities contribute to the decision process regarding voting in municipal elections. The theoretical basis is centered on political marketing, reference groups, virtual communities, and the consumer purchase decision process, contextualized to electoral procedure choices. Exploratory empirical research with a qualitative approach was carried out through in-depth interviews with voters from the city of Cuiabá to identify how reference groups influence vote choice among Millennials. It was possible to observe that primary, aspirational and formal reference groups collaborate in the choice of vote; informal, dissociative and secondary groups make a smaller contribution.